A robust double-network hydrogel with under sea water superoleophobicity fabricated via one-pot, one-step reaction. Issue 27 (21st June 2016) - Li, Hao; Hao, Dezhao; Fan, Junbing; Song, Sufen; Guo, Xinglin; Song, Wenlong; Liu, Mingjie; Jiang, Lei
Abstract : A robust double-network (DN) hydrogel fabricated by a one-pot, one-step reaction is reported. Abstract : A robust double-network (DN) hydrogel fabricated by a one-pot, one-step reaction is reported. The DN hydrogels not only have high mechanical strength and extremely low underwater oil adhesion, but also exhibit excellent characteristics, such as short processing duration, moderate swelling and free shaping. The DN hydrogel is durable in artificial sea water, and its mechanical property can be easily adjusted by adjusting the crosslinking agent concentration. In addition, because a large number of free hydroxyl groups remain in their networks, the mechanical property of the hydrogel can be enhanced and repaired by presenting more glutaraldehyde in the system.